2004
DOI: 10.1002/cncr.11922
|View full text |Cite
|
Sign up to set email alerts
|

Stereotaxic implantation of 5‐fluorouracil‐releasing microspheres in malignant glioma

Abstract: BACKGROUND The authors developed a new method of drug delivery into the brain using implantable, biodegradable microspheres. The strategy was evaluated initially to provide localized and sustained delivery of the radiosensitizer 5‐fluorouracil (5‐FU) after patients underwent surgical resection of malignant glioma. In this study, the microspheres were implanted by stereotaxy into deeply situated and inoperable brain tumors. METHODS Ten patients with newly diagnosed, inoperable, malignant gliomas were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 36 publications
0
49
0
1
Order By: Relevance
“…Poly(lactic-co-glycolic acid) (PLGA)-based microparticles are steadily gaining in importance as advanced parenteral drug delivery systems, because they offer various major advantages, including: (i) the possibility to accurately control the resulting drug release kinetics over periods of days to months (1,2); (ii) complete biodegradability (avoiding the removal of empty remnants upon drug exhaustion) (3,4); (iii) good biocompatibility (5,6), even if directly administered into brain tissue (intracranially) (7,8); and (iv) easy administration (compared to implants) using standard syringes and needles. Various products based on PLGA-based controlled release microparticles are commercially available, for instance Lupron Depot, containing the anticancer drug leuprolide acetate for the treatment of prostate cancer, and Risperdal Consta containing the antipsychotic drug risperidone for the treatment of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(lactic-co-glycolic acid) (PLGA)-based microparticles are steadily gaining in importance as advanced parenteral drug delivery systems, because they offer various major advantages, including: (i) the possibility to accurately control the resulting drug release kinetics over periods of days to months (1,2); (ii) complete biodegradability (avoiding the removal of empty remnants upon drug exhaustion) (3,4); (iii) good biocompatibility (5,6), even if directly administered into brain tissue (intracranially) (7,8); and (iv) easy administration (compared to implants) using standard syringes and needles. Various products based on PLGA-based controlled release microparticles are commercially available, for instance Lupron Depot, containing the anticancer drug leuprolide acetate for the treatment of prostate cancer, and Risperdal Consta containing the antipsychotic drug risperidone for the treatment of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…For treating gliomas, up to 8 BCNU-impregnated polyanhydride implants (Gliadel ® wafers) are placed into the resection cavity after surgery [9]. Clinical trials have used up to 5 stereotactic injections per patient of 5-fluorouracil (5-FU)-containing microspheres into brain tumors [15,16]. One recent report on the placement of multiple doxorubicin implants into dog prostates indicated that multiple implants could be highly effective in locally delivering chemotherapy to potential tumors [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard it is important to note that with the Gliadel™ wafer there is no close contact between targeted brain tissue and the implant, which may impair the penetration of the chemotherapeutic drug from the implant into the tissue. It was recognised that smaller dimensioned polymeric carrier structures, which can be implanted directly into the brain tissue surrounding the tumour cavity, may improve the penetration of the drug from the polymeric carrier into the brain tissue [8]. Considering the limited diffusional penetration of drugs through the brain tissue, mathematical modelling and experimental studies have shown that, for example, the entire volume of a tumour 2 cm in diameter may be targeted with four peripherally placed implants, while the centrally placed single implant never reached 100% tumour coverage during a simulated treatment period of 8 days [9].…”
Section: Discussionmentioning
confidence: 99%